2010
DOI: 10.1186/1757-4749-2-13
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis: the relationship between the Helicobacter pylori dupA gene and clinical outcomes

Abstract: BackgroundIn 2005, the first disease-specific Helicobacter pylori virulence factor that induced duodenal ulcer and had a suppressive action on gastric cancer has been identified, and was named duodenal ulcer promoting gene (dupA). However, the importance of the dupA gene on clinical outcomes is conflicting in subsequent studies. The aim of this study was to estimate the magnitude of the risk for clinical outcomes associated with dupA gene.MethodsA meta-analysis of case-control studies which provided raw data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
63
4
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 27 publications
6
63
4
4
Order By: Relevance
“…In our report, the cagA gene also exhibited a significant association with another virulence factor, the dupA gene, which is a protecting factor against gastric cancer and which is associated with an increased risk for duodenal ulcer [26] Gomes, et al [27] also found a correlation between cagA-positive and dupA-positive strains, but the association was in patients with duodenal ulcers. In a meta-analysis, Shiota, et al [26] reported a higher prevalence of dupA in Western countries than in Eastern countries.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In our report, the cagA gene also exhibited a significant association with another virulence factor, the dupA gene, which is a protecting factor against gastric cancer and which is associated with an increased risk for duodenal ulcer [26] Gomes, et al [27] also found a correlation between cagA-positive and dupA-positive strains, but the association was in patients with duodenal ulcers. In a meta-analysis, Shiota, et al [26] reported a higher prevalence of dupA in Western countries than in Eastern countries.…”
Section: Discussionmentioning
confidence: 76%
“…In a meta-analysis, Shiota, et al [26] reported a higher prevalence of dupA in Western countries than in Eastern countries. The study performed by Gomes, et al [27] revealed an increased prevalence of dupA in Brazilian patients with chronic gastritis (92.3%) and gastric cancer (87.6%), a finding which differed from that provided by Lu et al (2005) in a study on strains from Colombia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews state a worldwide prevalence of dupA of ca. 50% and confirm that dupA is a risk factor for DU (13,27). However, several studies have failed to show a significant association between dupA status and gastroduodenal diseases (6,14,24).…”
mentioning
confidence: 77%
“…The association between dupA status and disease development is primarily observed in Asian country such as China, Korea, Iraq, and North India. Our meta-analysis showed that infection with dupA-positive H. pylori increased the DU risk (OR ϭ 1.41, 95% CI ϭ 1.12 to 1.76), particularly in Asian countries (OR ϭ 1.57, 95% CI ϭ 1.19 to 2.06), but not in Western countries (OR ϭ 1.09, CI ϭ 0.73 to 1.62) (27). In the present study, although the data regarding gastritis in the U.S. population are limited (3), we showed that the prevalence of dupA in the U.S. population was 69.4%, which is relatively higher than that reported in other countries (13,27).…”
Section: Discussionmentioning
confidence: 99%
“…For different H. pylori strains, cagA-positive strains were associated with increased GC risk (Huang et al, 2003;Xu et al, 2006), but not dupA positive strains (Hussein et al, 2010;Shiota et al, 2010). A meta-analysis (Fuccio et al, 2009) based on two RCTs showed that the pooled result of H. pylori eradication in the prevention of GC was 0.46 (95%CI 0.26 to 0.82), suggesting that H. pylori eradication reduced GC risk.…”
Section: Discussionmentioning
confidence: 99%